2022
DOI: 10.5812/aapm.123112
|View full text |Cite
|
Sign up to set email alerts
|

Novel Local Anesthetics in Clinical Practice: Pharmacologic Considerations and Potential Roles for the Future

Abstract: : The treatment of pain, both acute and chronic, has been a focus of medicine for generations. Physicians have tried to develop novel ways to effectively manage pain in surgical and post-surgical settings. One intervention demonstrating efficacy is nerve blocks. Single-injection peripheral nerve blocks (PNBs) are usually preferred over continuous PNBs, since they are not associated with longer lengths of stay. The challenge of single injection PNBs is their length of duration, which at present is a major limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…4 In addition, bupivacaine is slowly released over several days following injection. 18 Although the local anesthetic lasts for a few hours, it can promote a reduction in sensitization, with a lasting effect. The authors of one study observed a gain in the range of motion over 24 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 In addition, bupivacaine is slowly released over several days following injection. 18 Although the local anesthetic lasts for a few hours, it can promote a reduction in sensitization, with a lasting effect. The authors of one study observed a gain in the range of motion over 24 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Pain relief after the block was also maintained for 3 months in a meta-analysis 4 . In addition, bupivacaine is slowly released over several days following injection 18 . Although the local anesthetic lasts for a few hours, it can promote a reduction in sensitization, with a lasting effect.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, there has been increasing research into novel drug delivery systems, with a goal of increasing the duration of local anesthetics. For example, the development of liposomal bupivacaine may lengthen nerve block durations, the clinical significance of which is still under investigation 87 . While most of this research is currently focused on topics out of the scope of this review, such as nerve blocks and postoperative pain control, investigations into polymer nanocarriers will likely impact numerous drug classes and guide future pediatric research in this arena.…”
Section: On the Horizonmentioning
confidence: 99%
“…Other novel experimental preparations as HTX-011 [13][14][15], a combination of bupivacaine and meloxicam, or naturally occurring reversible sodium channel blockers as tetrodotoxin [16,17] or neosaxitoxin [18], have been studied. Even though these novel substances have shown success in theoretically prolonging the duration of action of local anaesthetics, future research will be needed to prove their efficacy and safety in clinical studies [19,20].…”
Section: Sustained-release Local Anaestheticsmentioning
confidence: 99%